Parturition in Q.S Maryam: 22-26 According to the Tafsir of the Ministry of Religion of the Republic of Indonesia - Padurohman Azis, Fauzan; Purnama, Agung; Rofi, Muhammad Waliyuddin; Burhanudin, Ade; Murobhi, Jauzi Rofa; Purwati, Puji (Journal of Ulumul Qur'an and Tafsir Studies, 2024)
The article discusses childbirth in the Quran, focusing on Surah Maryam: 22-26. It explains that when Maryam felt the pain of childbirth, she leaned on a date palm tree and ate the dates that fell. These actions have similarities with medical practices, where leaning position is beneficial for the mother during childbirth, and eating dates can replenish energy lost during childbirth. The study in the article employs a qualitative method of comparative study with a literature review approach. Data sources include Tafsir Kemenag (Ministry of Religious Affairs' Interpretation) and obstetrics books. Data collection techniques involve searching, while content analysis is used for analysis.